2017
DOI: 10.1037/abn0000247
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-induced affect modulation in nonwithdrawn smokers with posttraumatic stress disorder, depression, and in those with no psychiatric disorder.

Abstract: This research sought to determine whether smoking influences affect by means other than withdrawal reduction. Little previous evidence suggests such an effect. We surmised that such an effect would be especially apparent in posttraumatic stress disorder (PTSD) and major depressive disorder (MDD), two disorders that are frequently comorbid with smoking and that involve dysregulated affect. Participants were US veterans who were regular smokers (N=159): 52 with PTSD (58% with comorbid MDD); 51 with MDD, and 56 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 101 publications
(174 reference statements)
1
8
0
Order By: Relevance
“…Of those studies, ten found that individuals with PTSD do not smoke a higher number of cigarettes than those without this condition, and one study reported that a diagnosis of PTSD was not associated with cigarettes smoked per day. Again, when exploring the comparison groups we found that most were vulnerable populations including individuals who are homeless (Baggett et al, 2016), individuals exposed to a traumatic event (Baschnagel et al, 2008;Beaudoin, 2011;Farris, 2015;Ritter et al, 2011), and individuals with current or prior diagnosis of a psychiatric disorder (Cook et al, 2017;Marshall et al, 2008;Marshall et al, 2009;Mitchell et al, 2012;Wilson et al, 2014). Finally, one study found mixed results wherein individuals with PTSD smoked more heavily than those without this condition (Zvolensky et al, 2008), but not more than individuals with another anxiety disorder.…”
Section: Heaviness Of Tobacco Usementioning
confidence: 90%
See 2 more Smart Citations
“…Of those studies, ten found that individuals with PTSD do not smoke a higher number of cigarettes than those without this condition, and one study reported that a diagnosis of PTSD was not associated with cigarettes smoked per day. Again, when exploring the comparison groups we found that most were vulnerable populations including individuals who are homeless (Baggett et al, 2016), individuals exposed to a traumatic event (Baschnagel et al, 2008;Beaudoin, 2011;Farris, 2015;Ritter et al, 2011), and individuals with current or prior diagnosis of a psychiatric disorder (Cook et al, 2017;Marshall et al, 2008;Marshall et al, 2009;Mitchell et al, 2012;Wilson et al, 2014). Finally, one study found mixed results wherein individuals with PTSD smoked more heavily than those without this condition (Zvolensky et al, 2008), but not more than individuals with another anxiety disorder.…”
Section: Heaviness Of Tobacco Usementioning
confidence: 90%
“…Four studies found no difference in levels of dependence between individuals with PTSD and those with other conditions, such as anxiety or depression (Marshall et al, 2008;Marshall et al, 2009;Young-Wolff et al, 2014;. Finally, one study found higher levels of nicotine dependence among individuals with PTSD compared to those with no psychiatric condition, but there no differences compared to individuals with major depressive disorder (Cook, Baker, Beckham, & McFall, 2017).…”
Section: Nicotine Dependencementioning
confidence: 92%
See 1 more Smart Citation
“…Cigarette smoking is highly prevalent in individuals with PTSD (Beckham, 1999), and smokers with PTSD report higher levels of anxiety and depression (Beckham et al, 1995). Past research has shown that smoking can temper negative affect following a negative mood induction task (Cook et al, 2017), and smoking is associated with decreased cravings, PTSD symptoms, and negative affect in the presence of trauma-related imagery (Beckham et al, 2007). The use of a sample of smokers could limit generalizability to other clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…Higher cravings, negative affect, and PTSD symptoms are associated with trauma-related imagery in groups with and without PTSD, and smoking is associated with decreased cravings, PTSD symptoms, and negative affect in the presence of trauma-related imagery (Beckham et al, 2007). Research has also shown that motivation to smoke can underlie relationships between negative affect and PTSD, in that individuals might be motivated to smoke to regulate negative emotionality experienced due to PTSD (Mahaffey et al, 2016) or acute stressors (Cook et al, 2017). As PTSD and negative affect are reportedly high in cigarette smokers, examining the moment-to-moment relationship between these variables merits examination in this sample.…”
Section: Introductionmentioning
confidence: 99%